Pengembangan Media Pembelajaran Berbasis Android pada Mata Pelajaran Bahasa Indonesia Kelas VII D di SMPN 2 Semparuk - Saedah Saedah; Lizawati Lizawati; Saptiana Sulastri (Ksatra: Jurnal Kajian Bahasa dan Sastra, 2024)
This development research is research which is the development of Android-based learning media which aims to help and see students' responses when given new media so that researchers can overcome the problems faced by teachers at school. This research is RND research which has a 4D design (define, design, develop, and disseminate). This research is located in the Sambas district of West Kalimantan, precisely at SMPN 2 Semparuk. The focus of the problem in this research was that from the beginning, the researcher started doing an internship and looked at the problems in the class, by looking at the responses of students who were bored with learning, the researcher tried to find a way out of the problem and thus created the development of Android-based learning media to support the Merdeka curriculum which prioritizes student creativity in learning. Android-based learning media for Indonesian language subjects, fiction and non-fiction book material, has been tested for suitability by three media experts, obtaining an overall average of 95% in the "Very Appropriate" category. Meanwhile, the results of testing by three material experts obtained an overall average of 93% in the "Very Good" category. The results of student responses with an overall score of 94% are included in the "Very Good" category. So overall it can be concluded that the learning media developed is very suitable for use in the Indonesian language learning process in fiction and non-fiction material.